PENARAPAN LQ DAN SHIFT SHARE DALAM MENGUKUR PERTUMBUHAN EKONOMI DI PROVINSI SULAWESI SELATAN PERIODE TAHUN 2013-2017 - Muh Fuad Randy; Muh. Indra Fauzi Ilyas; Abdul Sumarlin (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
Testing the Application of Location Quotient (LQ) and Shift Share in Measuring Economic Growth in South Sulawesi Province for the 2013-2017 Period. Based on the fluctuating conditions of labor changes and the contribution of GDP to the structure of the economy in the provinces of South Sulawesi and Indonesia. The main problem in this study is; What is the economic growth of South Sulawesi province based on the shift share approach for the 2013-2017 period, what is the economic growth of South Sulawesi province based on the LQ approach for the 2013-2017 period, the results of the calculation of GRDP 2013-2017 that have been made can be concluded as follows; There are 8 (eight) sectors which are the base sectors including the first sector of agriculture, both water supply, waste management, waste and recycling, third construction, fourth information and communication, fifth real estate, sixth government administration, defense and social security, seven services Education, eight health services and social activities there are four sectors that have the advantage of the first, namely the agricultural sector, the second processing industry, the third construction sector, the fourth large and retail trade, car and motorcycle repair